(untitled) (Research, Society and Development, 2020)
Objective: To establish the epidemiological characteristics and predictive factors of lethality of victims of severe TBI, admitted to the ICU of a Reference Hospital in the State of Piauí, during the period from January 2014 to December 2014. Methodology: is a descriptive and retrospective study. Data will be collected through medical records and noted in a standardized form. Results: The data analyzed showed young male adults, about 88.5%. There was a higher prevalence of severe TBI (18.4%), due to the research scenario: the intensive care environment. Motorcycle accidents were the main cause of TBI (75.9%). Regarding tomographic findings on ICU admission, there was a predominance of Extradural Hematoma (HED), followed by Acute Subdural Hematoma (HSDA). Conclusion: The research showed that the predictors of lethality in this population were mechanical ventilation time and blood transfusion.